An investigation of international and domestic tourists' satisfaction in heritage context: implications for destination marketing - Norzalita Abd Aziz,; Ahmad Azmi.M Ariffin,; Nor Asiah Omar,; Siow, Kim Yoon (Penerbit Universiti Kebangsaan Malaysia, 2011)
The marketing of heritage coincides with the emergence of marketing as an academic discipline in the 1950s. This research seeks to determine domestic and international tourists' expectations and perceptions of the heritage site of Melaka in Malaysia by measuring their satisfaction level using eight travel attributes. This study examines the overall satisfaction among international and domestic tourists who visited Melaka using a conceptual model that combines the concepts of the Expectancy Disconfirmation Paradigm and Service Quality framework. A sample of 322 respondents was surveyed with a structured questionnaire. A series of analyses were performed on both domestic and international tourists groups. It is important to understand that the R-square value obtained in the perception-only or perceived performance model is higher compared to Expectancy Disconfirmation Paradigm approach in determining tourists' satisfaction. By using the perceptions-only model for predicting overall satisfaction, the results showed that there are two factors namely 'Attractions' and 'Climate & Image' that appealed to international and domestic tourists. Theoretical, managerial and marketing implications of tourists' satisfaction in visiting heritage sites are discussed.